Уметноста како интерактивен процес - Ноневски, Вангел (Macedonian Academy of Sciences and Arts, 2018)
The contemporary work of art has found itself in a situation where it must renegotiate its ontological foundations in the age of digital reproduction, because its aura is now being additionally blurred by the digital replica (not only by the mechanical one). Therefore, we can’t expect that the reception of artworks will still continue to be “pure” and stable, according to the classical understanding of the notion. The new consideration of aesthetic reception should bare in mind the essentially interactive properties of new media. Because new media art or digital art should be considered as a sort of interface between the machine and the public, its aura (ontology) should rise from the interactive connection between the architects of the virtual reality of databases and the consumers who gain access to it. Therefore, the thing that today is considered to be a work of art is in fact a work of context: artists provide unfinished “art contexts” (even in cases where works are initially not envisaged as contexts, but rather as ordinary works of art) for others to complete and/or to put through an endless cycle of deconstruction, recontextualization, restructuring, reshaping... Consequently, although semantic deconstruction still plays a large role and effectively is a basic ontological factor of aesthetic legitimacy in digital art, it still has to be diversified from the semantic virtualization which dominates in interactive arts. Conclusion: The semantic virtualization means that aesthetic communication is no longer based solely on interpretation and deconstruction of the meaning of works of art, but rather on direct participatory advantage-taking of the contexts that are provided by them.
Art as an Interactive Process
Keywords: interactive art, semantics, aura, digital reproduction, new media, ontology, interactive context, modern art, deconstruction, virtualization